Recurrent pericarditis: a case report and literature review - Katinaitė, Justina; Petrauskienė, Birutė (Acta medica Lituanica, 2017)
Background. Recurrence affects about 30% (20% to 50%) of patients within 18 months after the initial episode of acute pericarditis resulting in subsequent rehospitalizations. Bearing in mind high treatment costs of patients admitted to hospital with acute and recurrent pericarditis, there is a need to optimize the treatment of both of these conditions. Materials and methods. We present a case of recurrent pericarditis. The first episode of pericarditis was diagnosed in 2006. Three months later the patient was hospitalized due to clinical symptoms suggesting recurrence of a past condition. Ten years after the initial episode of acute pericarditis the patient was hospitalized for the treatment of recurrent pericarditis. The search for etiology of the disease was unsuccessful, the patient received treatment with nonsteroidal anti-inflammatory drugs; empiric antimicrobial therapy was also administered. Results and conclusions. Acute pericarditis is the most common disease of the pericardium encountered in clinical practice. Colchicine has been demonstrated as a first-line drug to be added to conventional anti-inflammatory therapies in patients with a first episode of pericarditis or its recurrences in order to improve the response to therapy and reduce recurrences. Despite a large amount of new data, there are still several issues that require additional research and clarification, including the search for new individualized therapies, the best duration of treatment for patients with pericardial diseases, and optimization of patient follow-up in order to collect data on long-term outcomes that would allow shortening the duration of in-patient treatment and reduction of recurrences.